2015
DOI: 10.1016/j.sbspro.2015.01.203
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Interaction and Learning Performance as Determinants of Academic Achievement

Abstract: This investigation aims to relate teacher competencies, student-student interactions and learning performance, and its direct and indirect effects on academic achievement of high school students. A quantitative research was carried out, involving a representative sample of 1986 students attending Secondary Education Schools located in the central region of Portugal. The results obtained through the structural model show that perceived teacher competencies influence student-student interactions and learning per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
10
0
5
Order By: Relevance
“…These results are consistent with those that Cardoso et al (2011) and Costa et al (2015) obtained and which also showed a moderate association between student-student interaction and learning performance and between the latter and the students' academic results, indicating greater learning when students are involved in the educational process and when they interact positively with their peers.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with those that Cardoso et al (2011) and Costa et al (2015) obtained and which also showed a moderate association between student-student interaction and learning performance and between the latter and the students' academic results, indicating greater learning when students are involved in the educational process and when they interact positively with their peers.…”
supporting
confidence: 92%
“…As shown in several studies (Abrantes et al, 2007;Cardoso, Ferreira, Abrantes, Seabra, & Costa, 2011;Cornelius-White, 2007), there is an association between a positive teacher-student pedagogical interaction and the resulting learning. There is also a positive association between a good relationship among peers and students' learning outcomes (Cardoso et al, 2011;Costa, Cardoso, Lima, Ferreira, & Abrantes, 2015;Hay et al, 2004).…”
Section: Pedagogical Interaction and Learning Outcomesmentioning
confidence: 99%
“…Studies of pedagogical interaction today deal with different aspects (Bašaragin & Savić, 2019;Costa et al, 2015;Herrle, 2013;Klattenberg & Mcdowell, 2019;Kudryashova, 2016;Munarbayeva, 2015;etc. ).…”
Section: Resultsmentioning
confidence: 99%
“…Para akhli pendidikan sepakat bahwa prestasi belajar pada dasarnya merupakan hasil dari perbuatan belajar atau dapat pula dikatakan sebagai akibat dari perbuatan belajar yang dijalaninya. Prestasi belajar mencerminkan kemampuan siswa secara individu dalam mengusai pengetahuan, keterampilan termasuk sikapnya, sebagaimana pendapat yang mengemukakan bahwa Prestasi belajar adalah hasil yang diperoleh (Djaramah, 2008), dari akusisi keterampilan, pengetahuan dan sikap dalam bentuk skor yang diperoleh pada tes dalam subyek tertentu (Hsiang Feng, 2013).Prestasi belajar dapat menjelaskan nilai yang diperoleh siswa (Costa, Paula, Pedroso, & Ferreira, 2015). Dengan demikian prestasi belajar digunakan untuk mengetahui, memahami dan mampu menunjukan apa yang sudah diperoleh atau keberhasilan yang sudah dicapai (Gudeva & Dimova, 2012).…”
Section: Prestasi Belajar Siswaunclassified